Revisiting nonlinear impedance in acoustic liners - Roncen, Rémi (Journal of sound and vibration, 2025)
Acoustic liners are essential for sound dissipation in aeroacoustic applications, but their impedance response often displays significant nonlinearity under varying sound pressure levels. This study investigates the impact of complex source excitations on the nonlinear impedance of aeroacoustic liners. Using both experiments and the Impulse Response Time-Domain Impedance Boundary Condition (IR-TDIBC) model, the paper explores how varying spectral content, including multitone excitations with different phase configurations, influences the impedance characteristics of liners. Experimental results are compared with theoretical predictions, revealing strong alignment and highlighting the significant role of excitation phase and amplitude in shaping the impedance response. It is the time-domain instantaneous particle velocity at the liner interface that proves to be the primary determinant of the nonlinear response, and the sole input required by the IR-TDIBC. Additionally, the influence of the shear grazing flow noise on the impedance is examined by superimposing a single-tone excitation on background flow noise at different Mach numbers. Flow-induced noise is found to increase resistance and decrease reactance, as observed in duct experiments, accounting for some of the changes in impedance under shear grazing flow conditions. These findings underscore the importance of considering both complex source excitations and flow-induced noise when modeling the impedance of aeroacoustic liners, with implications for improving the accuracy of impedance predictions in practical aeroacoustic applications. [Display omitted] •IR-TDIBC model captures nonlinear acoustic liner impedance subject to complex sound fields.•Shows the complex influence of noise level and phase on nonlinear liner impedance.•Instantaneous velocity is shown as essential for accurate nonlinear impedance modeling.•Approach offers insights into turbulence-induced noise effects on liner impedance.•Provides a pathway for time-domain modeling of liners in realistic aeroacoustic setups.